IMPLEMENTASI PENGOLAHAN CITRA PADA WARNA MINYAK TRANSFORMATOR PADA PT. PLN (Persero) CABANG AMBON UNTUK MENGETAHUI UMUR MINYAK - Rina Latuconsina; Abraham Latumahina (Politeknik Aceh, 2017)
The quality of the transformer oil is very important in ensuring the continuity of operation and the life of a transformer. As a transformer oil insulation medium must meet the requirements such as the higher the penetration value the better the quality of the insulation. If the value of water content is too high then the water can reduce the breakdown voltage, and damage the insulation of transformer paper, so it can affect the color change on transformer oil. In addition, changes in the color of transformer oils are also influenced by the carbon content that occurs due to continuous heating in the transformer. Changes in the color of the transformer oil inevitably decrease the quality and durability of the transformer oil itself. The using of this digital image processing is to analyze the quality of Transformer oil based on Color on transformer oil. Where from the color shown by the transformer oil will be known the feasibility of transformer oil itself. The software design of the color information processing of the transformer oil image in this research was conducted by using Borland Delphi 7 due to its convenient and simple process. The result of the digital image processing in the color information from the transformer oil image with RGB (Red, Green and Blue) value have shown the transformer oil quality itself.